Spiritual Literature of the Peoples of the North Caucasus and the Culture of the East - Abdullatipov, Abdul-Kadyr Yu.; Adzhamatova, Nina K.; Akamov, Abusupyan T.; Alieva, Alla I.; Khugaev, Irlan S. (Journal of History Culture and Art Research, 2017)
The article poses the problem of connection between the spiritual culture of the peoples of the North Caucasus and the culture of the East. The authors show the historical predetermination of this process, their aim is to solve the problem of forming the North Caucasian literary tradition as a whole, to characterize some of its aspects, in particular, such as the originality of distribution of the Arabic language, the development of Arabic-language literature, its role and character in the process of strengthening the Middle East Caucasian, North Caucasian contacts, North Caucasian literature in Arabic (mainly), Persian, Turkic languages, the formation and development of its genre forms. The authors note that the driving forces of the Arab-Muslim culture - the Arabic language and Islam - have penetrated into Dagestan and the North Caucasus along with the Arab campaigns. The Arabic language and Islam became an integral part of the culture of many Dagestani and North Caucasian peoples. Islam was one of the main, but not the only factor that determined the prospects for cultural interaction. The ethnic and linguistic diversity of Dagestan and the North Caucasus facilitated the wide dissemination of the Arabic language as a communication mean accessible to a large part of the population, in particular, to the clergy. The process of intraregional interaction of literatures is gaining momentum. Therefore, this influence has gradually created the local original literature in the Arabic language in Dagestan, Chechnya, Ingushetia, and in part of Kabarda and Circassia. The authors of this article trace the ideological and aesthetic originality of this regional national literature.